IMPLEMENTASI AKUNTABILITAS DAN TRANSPARANSI PADA BAZNAS KOTA PAYAKUMBUH - Rahmi.S Rahmi.S; Nurul Fauzi; Alimin Alimin (Ensiklopedia of Journal, 2026)
The core issue of this thesis is the implementation of accountability and transparency principles in the management of zakat, infaq, and alms (ZIS) by the National Board of Zakat (BAZNAS) of Payakumbuh City. This study aims to identify and understand the implementation of these principles in ZIS management within the organization.This research employs a field research design with a descriptive qualitative method. Data collection techniques include interviews and documentation. Data analysis follows the interactive model developed by Miles and Huberman (1994), involving data reduction and presentation in brief narrative forms. To ensure data validity, the researcher utilized the triangulation technique.The results of the field research indicate that BAZNAS Payakumbuh City has implemented vertical organizational accountability in managing ZIS funds, yet horizontal accountability remains unfulfilled. Furthermore, BAZNAS Payakumbuh City has not fully applied the principle of transparency. The existing information system is limited to internal use, while an adequate external information system is currently lacking. Furthermore, mechanisms to ensure openness and facilitate public access to zakat management information have not yet utilized integrated information technology.Keywords: Accountability, Transparency, ZIS Management, BAZNAS